Decreased absolute number of peripheral regulatory T cells in patients with idiopathic retroperitoneal fibrosis - Liu, Lu; Yan, Huanhuan; Wang, Yanyan; Xie, Yuhuan; Jiang, Lei; Zhao, Jinfang; Gao, Chong; Li, Xiaofeng; Wang, Caihong (Frontiers in Immunology, 2022)
Objective: In order to determine whether the immune balance of T helper 17(Th17)/ regulatory T(Treg) is related to the pathogenesis of idiopathic retroperitoneal fibrosis(IRPF), we analyzed the differences in peripheral blood lymphocytes, CD4+T cell subsets and cytokines between patients with IRPF and healthy people to clarify the CD4+T cell subsets, especially Treg cell subsets, and the role of cytokines in the pathogenesis of IRPF. Methods: This study included 22 patients with IRPF, 36 patients with IgG4-related diseases(IgG4-RD) without retroperitoneal fibrosis(RPF), and 28 healthy controls. The absolute numbers and percentage of peripheral blood lymphocyte subsets and CD4+T cell subsets in each group were detected by flow cytometry, and the serum cytokine level was detected by flow cytometric bead array(CBA). Results: Compared with the healthy group, the absolute value of B cells in peripheral blood of IRPF patients was significantly decreased, and T, natural killer (NK), CD4+ and CD8+ were not significantly abnormal. The absolute numbers of Th2 cells was lower than healthy group(p=0.043). In particular, the absolute numbers of Treg cells was significantly lower than healthy group(p<0.001), while the absolute numbers of Th17 cells increased(p=0.682). Th17/Treg was significantly higher than healthy group(p< 0.001). Cytokine analysis showed that the level of interleukin(IL)-4 in IRPF patients was higher than healthy group(p=0.011), IL-6, IL-10, IL-17, TNF-α and IFN-γ were significantly higher than healthy group(all p<0.001). Receiver operating characteristic (ROC) curves showed that IL-10 and TNF-α could distinguish bilateral ureteral dilatation in IRPF patients, with areas under the ROC curve (AUCs) of 0.813 (95% CI:0.607-1.000, p=0.026) and 0.950 (95% CI:0.856-1.000, p=0.001), respectively. IL-6 could distinguish bilateral ureteral obstruction, with an AUC of 0.861 (95% CI: 0.682-1.000, p=0.015). Conclusions: Our study showed that IRPF patients had reduced Treg cells and indeed had Th17/Treg imbalance, which may be related to the pathogenesis of the disease. The levels of IL-6, IL-10 and TNF-α appear to be associated with the progression of IRPF.